Urethral erosion of a bone screw after internal urethrotomy: a rare complication after pelvic trauma - Onur, R.; Yilmaz, E.; Onur, M. R.; Orhan, I. (Springer London Ltd, 2010)
Background Although screw breakage or loosening are rarely encountered, they were reported to occur after instability of the internal fixation. Methods A man with a history of traumatic pelvic fracture 6 months ago presented to our clinic with inability to void. An anterior urethral meatotomy was made and a calcified but intact screw was removed from the urethra. Conclusions Screw migration with urological manifestations are extremely rare and usually include bladder migration with a subsequent voiding of the screw. We present a case in which internal urethrotomy for posterior urethral stricture caused erosion of a bone screw into the urethra which was subsequently removed by anterior meatotomy.
Keywords: Trauma; Urethra; Erosion; Screw; Internal urethrotomy